2022
DOI: 10.1063/5.0076765
|View full text |Cite
|
Sign up to set email alerts
|

Near-field thermophotonic system for power generation and electroluminescent refrigeration

Abstract: Near-field thermophotonic (TPX) systems that replace the high-temperature emitter in the thermophotovoltaic systems with a light-emitting diode (LED) have been reported to achieve low-grade heat harvesting and electroluminescent cooling, respectively. Nevertheless, the requirements for the two functionalities are different, leading to challenges to coordinate them. In our work, we propose a near-field TPX system composed of the CdTe LED and InP photovoltaic (PV) cell to realize two such functionalities with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Then, the device cannot produce power anymore: this is what happens between 0.1 and 0.4 V. Such feature was not observed in previous papers. For the ones using 0D models 18,20 , SRH recombination lifetimes considered were high, Yang et al even stating that SRH recombinations were negligible in their case. In our previous paper 19 , the high doping levels limited the SRH recombination rate.…”
Section: Pv Cellmentioning
confidence: 94%
See 2 more Smart Citations
“…Then, the device cannot produce power anymore: this is what happens between 0.1 and 0.4 V. Such feature was not observed in previous papers. For the ones using 0D models 18,20 , SRH recombination lifetimes considered were high, Yang et al even stating that SRH recombinations were negligible in their case. In our previous paper 19 , the high doping levels limited the SRH recombination rate.…”
Section: Pv Cellmentioning
confidence: 94%
“…S3). While these values are low, it should be possible to partially suppress the below-bandgap resonances, for instance with the use of Pt thin films 20 . This would help to come closer to the above-bandgap efficiency, and limit the heat extraction issue.…”
Section: Pv Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic thermal emission control has attracted considerable attention in the fields of radiative cooling, 1 , 2 , 3 , 4 adaptive camouflage, 5 , 6 , 7 , 8 , 9 thermostats, 10 , 11 thermochromic smart windows, 12 , 13 , 14 spacecraft thermal control 15 , 16 and thermophotovoltaic cells. 17 , 18 , 19 Among various dynamic thermal emission devices, the VO 2 -based dynamic emitter is a promising representative, which undergoes a reversible metal-to-insulator transition (MIT) at a critical temperature T c (68°C for intrinsic VO 2 ). 20 , 21 The occurrence of MIT is always accompanied by a dramatic change in the optical properties, which transforms the phase-change material from an infrared lossless “insulator state” ( T < T c ) to an infrared lossy “metallic state” ( T > T c ).…”
Section: Introductionmentioning
confidence: 99%
“…In decades' developments, regarding these three parts, different system enhancement strategies have been proposed. Firstly, the frequency-tuning technique [2], multi-modal configuration [3], frequency-up conversion [4,5] and nonlinear design [6,7] have been employed to amplify the mechanical excitation input. It was shown that the nonlinear piezoelectric energy harvester with a purely resistive load offers a broader bandwidth [7].…”
Section: Introductionmentioning
confidence: 99%